The preparedness of the accountants from the Malaysian accountant general's department in moving towards accruals accounting / Muhammad Iqbal Mohamed Azhari - Mohamed Azhari, Muhammad Iqbal (2013)
The move from cash to accruals accounting in public sector was initially made by the Malaysian government in year 2011. When the government made the announcement, it gives a huge shock to the preparers of the governmental financial reporting. It is believed that by the year 2015, all public sectors in Malaysia would fully adopt the accruals accounting system. The time to prepare for the implementation process is short compared to other countries that have successfully implemented the accruals accounting in their public sector. This study is made to examine the preparedness of accountants in implementing the accruals accounting. The Liider's Contingency Model was constructed to explain the contributing factors that lead to the accounting innovation in governmental accounting system. The Model was used in this study to identify the implementation barriers that will slow down the implementation process. As identified in the Model, factors such as the qualified accountants are one of the implementation barriers. Thus, the result of this study shows that the accountant's attitude and the amount of training provided to the accountant is positively influence their preparedness in implementing accruals accounting. Even though the results show that the accountants' attitude are positive towards preparing for the implementation of accruals accounting, but there are concerns over the implementation of accruals accounting in public sector. Most of the accountants are highly concern on the employees' lack of knowledge. This shows that there is still a long way before Malaysia public sector successfully adopts the accrual accounting system.